Childhood obesity in Brazil: A literature review (Research, Society and Development, 2023)
Introduction: Childhood obesity is a growing disease in Brazil and around the world, being a public health problem. The WHO estimate is that this number will reach 11.3 million in 2025. Objective: To evaluate the panorama of childhood obesity in Brazil, nationally and regionally, as well as its causes. Methodology: The research was carried out in September 2023, 16,247 articles were found in the databases, and 14 articles were selected to make up this narrative bibliographic review. Results: It was observed that female children are more affected by obesity than male children. Furthermore, the Brazilian regions with the highest rates of childhood obesity are the South and Southeast regions. Conclusion: It is concluded that childhood obesity has been growing alarmingly in Brazil due to several factors and requires urgent action to combat this threat to public health and children's well-being.